Study the Association of Fat Mass and Obesity-associated (FTO) Gene Polymorphisms (SNP rs9939609) with Biochemical Markers in Obese Iraqi Patients - Hashim, Mohammad F.; Sabah, Fatima S.; Abbas, Hamid J. (Iraqi Journal of Science, 2024)
This study aimed to evaluate the association of single nucleotide polymorphisms (SNP rs-9939609) of the fat mass and obesity-associated (FTO) gene with body mass index (BMI) and some biochemical markers in obese patients. The fat and mass obesity (FTO) gene variant specific single nucleotide polymorphism (SNP rs-9939609) with the T to A missense mutation may have a powerful association with obesity. This case-control study included 106 obese patients (57 males and 49 females) and 80 healthy control (40 males and 40 females). DNA was extracted from whole blood, and then the tetra-primer amplification refractory mutation system - polymerase chain reactions (ARMS.PCR) technique was used to limit the single nucleotide gene polymorphisms (rs9939609) of the FTO gene. Lipid profile, glycated hemoglobin (HbA1C), fasting blood sugar, insulin and FTO concentrations were measured by standard methods. In this study, the A allele in the rs9939609 was at a higher frequency of 35 (33.1%) in the obese patients and at a significant p-value = 0.039 compared with control 15 (18.7%). It significantly increased in the additive model and allele frequency (p= 0.003, 0.002 respectively). The rs9939608 SNP showed a significant association with increased BMI, insulin and homeostatic model assessment-insulin resistance (HOMO-IR) with p-values of 0.001, 0.001 and 0.028 respectively. After making adjustments for age and sex, lower levels of high-density lipoprotein (HDL) were observed in the AA and TA genotypes compared to the TT genotype (p = 0.004). While, no significant differences were recorded between the rs9939608 SNP and HbA1C, total cholesterol (TC), triglyceride (TG), very low-density lipoprotein (VLDL), and low-density lipoprotein (LDL) in obese patients